Kariérová adaptabilita Její podoby, proměny, souvislosti a role v životě mladých dospělých procházejících středním odborným vzděláváním - Hloušková, Lenka (Masaryk University Press, 2020)
Title in English: Career adaptability: Its forms, changes, contexts, and roles in the lives of young adults undergoing upper-secondary vocational education Living in today's rushed time full of various changes increases the demands on the individual's ability to adapt to these changes. Career adaptability plays an important role in coping with changing demands in the field of work. What is career adaptability? Why is it important, and what does it affect? The answers to these questions and many others are provided in the monograph, entitled "Career adaptability: Its Forms, Changes, Contexts, and Roles in the Lives of Young Adults Undergoing Upper-Secondary Vocational Education," which is the first publication written on this topic in the Czech language. In the book, a team of authors presents the construct of career adaptability and the results of unique research carried out in the Czech Republic. In the first part, the reader may find an analytical overview of various concepts of career adaptability and related concepts. The central part of the publication is devoted to the results of quantitatively conducted longitudinal research, which aimed to identify career adaptability and its relationships to several demographic, school, relational, and personality variables in the case of students and later graduates of upper-secondary vocational education-those who are in the crucial stages of their career construction. Many empirical findings concentrated in this book are beneficial not only for the career counseling theories and research on career adaptability but also for vocational education or career counseling practitioners.